Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/cncr.31696
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiovascular disease among Nordic childhood cancer survivors with diabetes mellitus: A report from adult life after childhood cancer in Scandinavia

Abstract: BACKGROUND: Childhood cancer survivors have an increased risk of cardiovascular disease (CVD) and diabetes mellitus. Because diabetes is a potentially modifiable risk factor for CVD in the general population, it is important to understand how diabetes affects the risk of CVD among childhood cancer survivors. METHODS: This study examined the risk of CVD among survivors with diabetes and 142,742 population comparison subjects. From the national cancer registries of the 5 Nordic countries, 29,324 one-year survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Exposure to cytotoxic agents and radiation have rendered childhood cancer survivors at an increased risk of developing cardiovascular disease, metabolic syndrome, diabetes, hypertension and other conditions as a result of long-term vascular complications. [36][37][38][39] In this study, we have shown that clinical biomarkers of CVD are significantly elevated in young adult survivors of childhood leukemia.…”
Section: Discussionmentioning
confidence: 68%
“…Exposure to cytotoxic agents and radiation have rendered childhood cancer survivors at an increased risk of developing cardiovascular disease, metabolic syndrome, diabetes, hypertension and other conditions as a result of long-term vascular complications. [36][37][38][39] In this study, we have shown that clinical biomarkers of CVD are significantly elevated in young adult survivors of childhood leukemia.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, cancer survival should be considered an independent CV risk factor [ 103 ]. A proinflammatory and hypercoagulable condition with increased platelet activation and aggregability typically occurs in cancer, increasing the prevalence of ACS [ 72 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, the number of children surviving brain tumors has reached record rates. However, survivors are at risk of developing obesity, cardiovascular disease, and type 2 diabetes mellitus 9 , 10 , 27 32 . While childhood obesity and dysglycemia drive early adult mortality 33 , SCBT have higher rates of adverse cardiometabolic outcomes and premature mortality than the general population but with similar BMI-defined obesity rates 9 , 10 , 16 , 27 32 , 34 .…”
Section: Discussionmentioning
confidence: 99%